Generalized Polarized Manifolds - Awane, Azzouz (Revista Matemática Complutense, 2008)
We introduce and develop the notion of generalized Poisson manifolds and analyze their main properties. Several generalized Hamiltonian maps for polarized Poisson manifolds and vectorial Hamiltonian maps for systems in dimension smaller or equal than 4 are given.